Potential of Antibacterial Activity in Natural Ingredients (Betel Leaves, Basil Leaves, Avocado Seeds, Lemongrass, Garlic) As Natural Hand Sanitizers: Journal Review - Dwi Febri Pranoto; Oldy Fristian Famly; Chandra Akbar; Erna Astuti (Universitas Ahmad Dahlan, 2021)
In an effort to reduce the use of alcohol-based hand sanitizers because of their quite dangerous impact on the skin, natural hand sanitizers are an alternative. The antibacterial substances in betel leaves, basil leaves, avocado seeds, lemongrass, and garlic can be used as materials for natural hand sanitizers. The purpose of this study was to collect, identify, and compare journals about the effectiveness of antibacterial agents in natural ingredients that are used as natural hand sanitizers. Using the journal review method through reviewing the contents of journals that discuss antibacterial activity, the results show that the five phytochemical compounds contain active antibacterial compounds so that they have the potential to make natural hand sanitizers, as well as the antibacterial inhibition zone of these five ingredients showing high results with strong to very strong categories. It was concluded that the five ingredients could be used as natural hand sanitizer materials. However, betel leaves are preferred because of their largest inhibition zone, 3.1-4.0 cm.